The shortcut : why intelligent machines do not think like us - Cristianini, Nello (Boca Raton : CRC Press, 2023)
"One of the most influential scientists in the field of artificial intelligence explains its fundamental concepts and how it is changing culture and society. A particular form of AI is now embedded in our tech, our infrastructure, and our lives. How did it get there? Where and why should we be concerned? And what should we do now? The Shortcut: Why Intelligent Machines Do Not Think Like Us provides an accessible yet probing exposure of AI in its prevalent form today, proposing a new narrative to connect and make sense of events that happened in the recent tumultuous past, and enabling us to think soberly about the road ahead. The book is divided into ten carefully crafted and easily digestible chapters. Each chapter grapples with an important question for AI. Ranging from the scientific concepts that underpin the technology to wider implications for society, it develops a unified description using tools from different disciplines and avoiding unnecessary abstractions or words that end with -ism. The book uses real examples wherever possible, introducing the reader to the people who have created some of these technologies and to ideas shaping modern society that originate from the technical side of AI. It contains important practical advice about how we should approach AI in future without promoting exaggerated hypes or fears. Entertaining, disturbing, but always thoughtful, The Shortcut confronts the hidden logic of AI while preserving a space for human dignity. Essential reading for anyone with an interest in AI, the history of technology, and that of ideas. General readers will come away much more informed about how AI really works today, and what we should do next"--
OCLC-licensed vendor bibliographic record.
Keywords: Artificial intelligence -- Social aspects; Intellect; Civilization, Modern -- 21st century; COMPUTERS / Neural Networks; COMPUTERS / Social Aspects / General; COMPUTERS / Social Aspects / Human-Computer Interaction